From Words to Worlds Exploring Constitutional Functionality - Breslin, Beau (Johns Hopkins University Press, 2009)
In the 225 years since the United States Constitution was first drafted, no single book has addressed the key questions of what constitutions are designed to do, how they are structured, and why they matter. In From Words to Worlds, constitutional scholar Beau Breslin corrects this glaring oversight, singling out the essential functions that a modern, written constitution must incorporate in order to serve as a nation's fundamental law.Breslin lays out and explains the basic functions of a modern constitution-including creating a new citizenry, structuring the institutions of government, regulating conflict between layers and branches of government, and limiting the power of the sovereign. He also discusses the theoretical concepts behind the fundamentals of written constitutions and examines in depth some of the most important constitutional charters from around the world. In assaying how states put structural ideas into practice, Breslin asks probing questions about why-and if-constitutions matter.Solidly argued and engagingly written, this comparative study in constitutional thought demonstrates clearly the key components that a state's foundational document must address. Breslin draws a critically important distinction between constitutional texts and constitutional practice.